Comprehensive characterization of genomic and radiologic features reveals distinct driver patterns of RTK/RAS pathway in ground‐glass opacity pulmonary nodules. Issue 11 (27th August 2022) - Yu, Fenglei; Peng, Muyun; Bai, Jing; Zhu, Xiuli; Zhang, Bingyu; Tang, Jingqun; Liu, Wenliang; Chen, Chen; Wang, Xiang; Chen, Mingjiu; Tan, Sichuang; Sun, Yi; et al.
Abstract: Ground‐glass opacity (GGO)‐associated pulmonary nodules have been known as a radiologic feature of early‐stage lung cancers and exhibit an indolent biological behavior. However, the correlation between driver genes and radiologic features as well as the immune microenvironment remains poorly understood. We performed a custom 1021‐gene panel sequencing of 334 resected pulmonary nodules presenting as GGO from 262 Chinese patients. A total of 130 multiple pulmonary nodules were sampled from 58 patients. Clinical‐pathologic and radiologic parameters of these pulmonary nodules were collected. Immunohistochemistry (IHC) and multiplex immunofluorescent staining (mIF) were applied to analyze proliferation and immune cell markers of GGO‐associated pulmonary nodules. Compared with pure GGO nodules, mixed GGO nodules were enriched for invasive adenocarcinoma (IAC) (182/216 vs 73/118, P  < .001). Eighty‐eight percent (294/334) of GGO‐associated nodules carried at least one mutation in EGFR/ERBB2/BRAF/KRAS/MAP2K1 of the RTK/RAS signaling pathway, and the alterations in these driver genes were mutually exclusive. The analysis of multifocal pulmonary nodules from the same patient revealed evidence of functional convergence on RTK/RAS pathways. Nodules with ERBB2 / BRAF / MAP2K1 mutations tended to be more indolent than those with EGFR and KRAS mutations. IHC and mIF staining showed that KRAS ‐mutant GGO nodules displayed higher infiltration of CD4+ T cell and CD8+ T cell as well as stronger proliferation and immune inhibitory signals. Our study demonstrates a driver landscape of radiologically detectable GGO‐associated pulmonary nodules in Chinese patients and supports that different driver patterns in RTK/RAS pathway are corresponding to different radiologic features. Abstract : What's new? Pulmonary lesions with ground‐glass opacity (GGO) detected on computed tomography (CT) are commonly observed in lung adenocarcinoma and its precursors. GGO are pathologically and molecularly diverse, though associations between their genetic and radiologic features remain poorly defined. Here, using a custom gene panel, the authors applied high‐depth sequencing to GGO‐associated pulmonary nodules revealed by CT in Chinese patients. Mutations in the RTK/RAS signaling pathway were present in 88% of GGO‐associated nodules. Distinct pathological, radiological and immune features of GGO‐associated nodules were defined by alterations in common driver genes in the pathway, namely EGFR, KRAS, BRAF, ERBB2 and MAP2K1 .